ESRA19-0198 Establishing a practical and affordable regional anaesthesia follow-up service. (30th August 2019) - Thompson, M; Ashken, T; Heppolette, C; Ng, SC; Harty, E
Abstract : Background and aims: Follow-up after regional anaesthesia (RA) is key to safe patient care. It can lead to improved outcomes and addresses patient satisfaction. In centres performing high numbers of RA, this can be prohibitively expensive and time consuming. At our institution, we aimed to establish a streamlined and affordable follow-up service managed by our block room team. Methods: We undertook a series of plan, do, study, act (PDSA) cycles and monitored patient responses. PDSA cycle 1. We trialled both telephone and text-message based follow up at 24 and 48 hours. PDSA cycle 2. We exclusively delivered a post-operative questionnaire via text-message and reduced the number of questions asked. PDSA cycle 3. W e changed the timing of the postoperative questionnaires to 48 hours and 7 days. PDSA cycle 4. We sent a text message (with a delayed chaser text) at 48 hours. Conclusions: Over 4 cycles of PDSA, we established that the best response rates were achieved when a text message, with a link to an online survey, was sent out at 48 hours. We included a second 'chaser' message if there was no response within 48 hours. We found that no further useful information was gained if patients were surveyed after this time point. Additionally, a 24 hour text-message was found to be too early to yield useful results. We have found an optimal method of engaging with our patient cohort. the opportunity for the system to be used for automatic clinical alerts and as a research tool will be part of our future work.